2010
DOI: 10.5210/fm.v15i7.2799
|View full text |Cite
|
Sign up to set email alerts
|

Pirates of Silicon Valley: State of exception and dispossession in Web 2.0

Abstract: This paper investigates a paradox in the reception of Web 2.0. While some of its services are seen as creators of a new informational economy and are hence publicly legitimized, other features are increasingly under surveillance and policed, although in reality the differences between these services is far from obvious. Our thesis is that we are currently experiencing a temporary postponement of the law, in the context of Web 2.0. Agamben’s work on the state of exception is here used to theorize the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…Digital 'pessimists' have, of course, long disputed that many social networking services, by transforming individual/private qualitative information (e.g., shopping preferences, travel destinations, biographical input) into quantitative public data that can be sold to and processed by third parties, give rise to pertinent concerns over unregulated commerce, surveillance and a centralization of power that is far less democratic or unpredictable than users or early optimistic theorizers tended to believe (see Turow, 2012;Jakobsson & Stiernstedt, 2010;Dijck & Nieborg, 2009;Fuchs, 2015, p. 378). Tumblr remains, for better or worse, a private enterprise, and while David Karp's commitment to the integrity of his brainchild seems extraordinary, many other dangers, from bankruptcy to corporate incompetence or greed, can lead to the medium's degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital 'pessimists' have, of course, long disputed that many social networking services, by transforming individual/private qualitative information (e.g., shopping preferences, travel destinations, biographical input) into quantitative public data that can be sold to and processed by third parties, give rise to pertinent concerns over unregulated commerce, surveillance and a centralization of power that is far less democratic or unpredictable than users or early optimistic theorizers tended to believe (see Turow, 2012;Jakobsson & Stiernstedt, 2010;Dijck & Nieborg, 2009;Fuchs, 2015, p. 378). Tumblr remains, for better or worse, a private enterprise, and while David Karp's commitment to the integrity of his brainchild seems extraordinary, many other dangers, from bankruptcy to corporate incompetence or greed, can lead to the medium's degradation.…”
Section: Discussionmentioning
confidence: 99%
“…I conclude by suggesting that there exists considerable potential for Tumblr communities to function as independent sites of knowledge (re)production, acting as non-commercial user archives, or reflexive and dialogical repositories of individually-filtered cultural content. My analysis thereby also attempts to offer a more positive, conciliatory perspective on the debates within new and social media, which tend to oscillate between optimism and pessimism (e.g., Fuchs, 2015;Gauntlett, 2015;Turow, 2012;Jakobsson & Stiernstedt, 2010; see also Hesmondhalgh, 2013, chapter 9).…”
Section: Introductionmentioning
confidence: 99%
“…So here we will tap into the ongoing discussion of how to understand the activity performed by everyday users of social media on Web 2.0 (often refer to as produsers) in relation to capitalist interests (cf. Fuchs 2009;Jakobsson and Stiernstedt 2010). The production of surplus value by exploiting the activity performed on social media sites such as Facebook, YouTube, etc.…”
Section: Dispossession Of Everyday Online Activitymentioning
confidence: 99%
“…As users of technology enter into tacit data license agreements with the firms that create and control the technology, they are dispossessed of the right to control those data. Jakobsson and Stiernstedt (2010) have suggested that all Web 2.0 technologies function through the process of accumulation by dispossession, but, here, we illustrate how it specifically functions through commodification and privatization in the generation of 'big data. '…”
Section: Data Accumulation Through Dispossession Commodifying Everydmentioning
confidence: 99%